Assessment of Tannery Based Chromium Eco-toxicity through Investigating Regional Bio-concentration in Commercially Produced Chicken Eggs and their Physical Properties (Bangladesh Journal of Scientific and Industrial Research, 2009)
In Bangladesh, among the routes of chromium eco-toxicity, feeds and fertilizer production from tanned skin-cut wastes is the most direct one leading to food chain contamination. The tanning industries of Hazaribagh are processing some 220 metric tons of hide a day with an associated release of 600 - 1000 Kg of tanned skin-cut waste (SCW) resulting from per ton processed hide. The SCW are protein-rich and are unscientifically used to produce protein-concentrates for poultry and fish feeds, and organic fertilizer. In view of the facts, a huge migration of chromium can happen into poultry products, fish and vegetables, and further bio-magnify into food chain. The target population of this phenomenon is also huge. Regional bio-concentration of chromium was investigated in commercially produced chicken eggs. Though the routes of distribution of this hugely produced protein-concentrates from SCW are unknown, eggs were sampled from Dhaka and its nearby other seven districts covering the central region of Bangladesh. Twelve eggs were randomly sampled from each district's egg stock market while albumen and yolk in each egg were studied separately for all studies. Out of the 192 samples from 96 eggs, dry weight basis mean chromium concentration was found to be 1.9016 ppm with a sample standard deviation of 0.1502. The concentration levels were ranged from maximum of 19.8051 ppm to undetectable levels. Single poultry egg was found to contain a mean chromium content of 23.3809 μg, which exceeds adequate daily dietary intake of children up to 8 years of age as well as corresponds to major part for other age groups. The region-wise physical properties of the eggs were also studied which included USDA size grading by whole weight at raw condition, whole weight ratio of raw condition to complete boiled condition, weight ratio of boiled shell-albumen-yolk, moisture content of albumen of boiled eggs, and moisture content of yolk of boiled eggs. The mean whole weights of eggs at raw condition were within the range of 39.9568 g ('peewee' as per USDA size grading) to 62.4047 g ('large' as per USDA size grading), the mean whole weight ratio of raw condition to complete boiled condition ranged between "1 : 0.9704" to "1 : 0.9782", the minimum weight ratio of boiled shell-albumen- yolk for all sample classes were ranged from "1 : 2.0714 : 1.1549" to "1 : 4.8810 : 2.0677" whereas the maximum weight ratio ranged from "1 : 3.1933 : 1.4557" to "1 : 7.8084 : 3.3818", the mean moisture content of albumen of boiled eggs varied within the range of 82.8876% to 84.7636%, and the mean moisture content of yolk of boiled eggs were between 50.6563% to 52.5124%. These properties are of importance for local-level as well as basic researches on poultry. Key words: Heavy metal bio-concentration, Ecotoxicology, Egg science   doi: 10.3329/bjsir.v44i1.2710 Bangladesh J. Sci. Ind. Res. 44(1), 11-30, 2009